2016
DOI: 10.1016/j.hkpj.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle energy technique and static stretching on pain and functional disability in patients with mechanical neck pain: A randomized controlled trial

Abstract: Background: Mechanical neck pain is one of the common musculoskeletal disorders. Muscle energy technique (MET) may be a useful intervention for treating such disorder. Objective: The aim of this study was to compare the effect of MET with passive stretching on pain and functional disability in people with mechanical neck pain. Methods: A randomized controlled trial was undertaken. Sixty patients with mechanical neck pain were randomly allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 24 publications
(32 reference statements)
10
51
1
2
Order By: Relevance
“…The outcome of this study revealed a considerable improvement in pain associated with NSCNP in both MET and NSE groups in comparison to the control group after 8 weeks of treatment. This is consistent with the findings of Phadke et al (18) who revealed that MET reduced pain in patients with non-specific neck pain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The outcome of this study revealed a considerable improvement in pain associated with NSCNP in both MET and NSE groups in comparison to the control group after 8 weeks of treatment. This is consistent with the findings of Phadke et al (18) who revealed that MET reduced pain in patients with non-specific neck pain.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there was an improvement in the neck disability in both MET and NSE groups compared to the control. This corroborates the findings of a previous study by Ylinen et al (27) on NSE and Phadke et al (18) on MET among CNP patients. The impact of MET was moderated by the afferent input from the proprioceptive sensory receptor organ, which occurs when a muscle is contracted isometrically, the afferent feedback inhibits the muscle, resulting in relaxation when the contraction is released.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…according to the international association for the study of Pain, this is neck pain in the area below the nuchal line and above the line marked by the transverse line running through the first spinous process of the thoracic spine and laterally through the sagittal plane adjacent to the lateral surface of the neck [4].…”
Section: Cervical Back Pain Syndromementioning
confidence: 99%
“…it has been shown that muscular imbalance (in the sternocleidomastoid, trapezius, levator scapulae, serratus anterior and pectoralis muscles) and abnormal movements may cause improper congruence of the articular surfaces. this can provoke pain, a secondary consequence of a primary imbalance in muscle tone [4]. incorrect axial loading of the articulat joints results in overloading of the intervertebral discs, followed by destruction of the intervertebral joints (the formation of osteophytes, increase of muscle tension, worsening of mobility, transfer of local ailments to peripheral areas -upper limbs, chest) [22].…”
Section: Cervical Spinementioning
confidence: 99%